Commodification of Advertorials in Tribun Sumsel’s 2024 Palembang Election Campaign - Desmalinda; Sulkhan, Khumaid Akhyat (UPT Publikasi Ilmiah UNISBA, 2025)
This study examines the phenomenon of content commodification in digital media, especially in advertorial practices that appear on the online media of the Tribun Sumsel during the 2024 Palembang Mayor Election campaign. The primary focus of the study is how advertorials, which are supposed to be a transparent form of advertising, further blur the line between news and advertising, which risks undermining journalistic objectivity. This study uses qualitative descriptive methods through in-depth interviews and content analysis to explore the dynamics of implementing journalistic firewall boundaries between the newsroom and the business space in the media. The findings show that the media is increasingly prioritizing commercial and political interests by producing content that cannot be distinguished from news and advertorial. This practice has the potential to reduce the credibility of the media and obscure the function of the press as an agent of power supervision. This study shows the importance of maintaining the difference in quality of the content of news texts and editorial texts to avoid information ambiguity by improving the quality of journalistic work. Because journalistic firewalls do not only refer to technical restrictions by emphasizing advertorial columns with news alone, but also by differentiating the writing quality of both. Maintaining journalistic firewalls is essential to ensuring that the media remains an objective and independent source of information for the public.